Penerapan Model Pembelajaran Berbasis Resource Based Learning Dalam Meningkatkan Kemampuan Berpikir Kritis Siswa Kelas X Pada Pelajaran PAI di SMANSATSET - Nur Hasyikin; Anjani Putri Belawati Pandingan; H. Muhammad Imam Syafi’i (Hidayah : Cendekia Pendidikan Islam dan Hukum Syariah, 2025)
This study aims to explore the implementation of the Resource-Based Learning (RBL) model in enhancing the critical thinking skills of tenth-grade students in Islamic Religious Education (PAI) at SMA Negeri 1 Sangatta Selatan. It also examines the factors that support or hinder the use of the RBL model among these students. A qualitative approach was used, with field research as the research type. Data sources included both primary and secondary materials. Informants consisted of Islamic Religious Education teachers and tenth-grade students. Data collection methods involved observation, interviews, and document analysis, and the data were analyzed descriptively. The findings reveal that the RBL model enables students to analyze information critically, engage more actively and reflectively with the material, enhance their logical thinking, deepen understanding, and develop the ability to find and evaluate appropriate solutions. Supporting factors for the model’s success include the availability of diverse learning resources, engaging teaching methods, teacher support as facilitators, and effective group collaboration and discussion. On the other hand, limited active participation from some students was identified as a barrier. Overall, the application of the RBL model significantly improved students’ critical thinking skills compared to traditional teaching methods. This was evidenced by an increase in the average critical thinking test scores in the experimental group. Therefore, the RBL model proves to be an effective alternative strategy for enhancing both the quality and outcomes of Islamic Religious Education at the high school level. Moreover, students showed greater engagement, improved collaboration skills, and increased independence in accessing and utilizing learning materials. These results highlight the effectiveness of the RBL model in fostering critical thinking and meaningful learning experiences in PAI subjects.